Introducing evidence-based planning. - Faludi, Andreas; Waterhout, Bas (TH Zürich, NSL, 2006)
Der Beitrag liefert eine Einführung in das Konzept der wissensbasierten Planung, wie es sich in Großbritannien in den1990er Jahren entwickelt hat und geht einigen seiner Vorläufer im Römischen Steuerwesen und dem berühmten Domesday Book nach. Er vermittelt die Zusammenhänge zwischen Wissen und Entscheidungsprozessen, Wissen und Handeln und befasst sich mit der Rolle der Forschung, der Kreativität und den sozialen Kontexten der Raumplanung. Er führt in die aktuelle Debatten um die Forderungen der Europäischen Verfassung nach einer wissenbasierten Entscheidungsfindung und den daraus resultuierenden wachsenden Forschungsaktivitäten verschiedener Institutionen (ESDP; ESPON) ein. Zugleich stellen die Ausführungen den Rahmen und die Einführung für die weiteren, vor allem länderbezogenen Fallstudien des Heftes dar. goj/difu

This article introduces the concept of evidence-based planning, in the context of its appearance in the UK at the end of the 1990s and traces its historical relationship to the practice of collecting information for state and public purposes from Roman taxation and the famous Domesday Book to the movements and counter-movements of the last century to its present role in politics and policy-making in the field of spatial planning. Delving, into the connections between evidence and decision-making, evidence and action, the use and role of research, creativity and social context as elements of spatial planning, the article also provides background on the perennial planning- theoretical debate. It leads into the current situation where the EU charter requires the use of the best scientific information available for decision-making and where the demand for research has increased since the year 2000 with corresponding, agencies (ESDP, ESPON) and institutions being created or reorganized to fill the information gap. Pointing out what is new about evidence-based planning and how it has changed from previous practices, this article builds a framework for the articles presented in this issue, which study and evaluate the theory and practice of evidence-based planning as one of the important trends of this century. difu
Keywords: Raumordnung; Raumplanung; Planungstheorie; Raumordnungspolitik; Planungspraxis; Planungsgeschichte; Planungswissenschaft